Identification and Expression of cGnRH-II Gene in Three Strains Osphronemus gouramy (Soang, Jepun and Bluesafir) - Rosita, Rita Eka; Syakuri, Hamdan; Nuryanto, Agus; Hilmi, Endang; Sukardi, Purnama; Prayogo, Norman Arie (Molekul, 2023)
Gouramy (Osphronemus gouramy) has very high economic value and is easy to cultivate. Currently there are about six strains that have been successfully cultivated based on their reproductive ability to produce eggs, namely goose (soang, goose gouramy), jepun (japan, japonica), blue sapphire, paris, bastar (broiler) and porcelain. One of the reasons for these differences in ability is internal factors which can be seen through the identification and expression of the cGnRH gene that each of these gouramy strains have. The cGnRH gene functions in signaling the pituitary gland to secrete the hormone GtH. This study aims to identify sequences and gene expression values ​​resulting from three strains of gouramyat different age levels. The research method used was the exploration of three gouramy strains (soang, jepun, blue sapphire) at different age levels (4 months, 8 months, 12 months), and three gouramy strains were taken for each age level. This research was conducted through several stages, namely organ preparation, isolation, sequence identification and measurement of cGnRH gene expression. Sequence data was analyzed using phylogenetic trees and gene expression was analyzed using One Way ANOVA test. The sequence results showed that the soang strain had a sequence that was more similar to the jepun strain than the blue sapphire strain, and the resulting gene expression showed that the three gouramy strains with three different age levels did not give different results.